2016
DOI: 10.13057/biodiv/d180101
|View full text |Cite
|
Sign up to set email alerts
|

Screening of rhizobacteria from rhizosphere of healthy chili to control bacterial wilt disease and to promote growth and yield of chili

Abstract: Abstract. Yanti Y, Astuti FF, Habazar T, Nasution CR. 2017. Screening of rhizobacteria from rhizosphere of healthy chili to control bacterial wilt disease and to promote growth and yield of chili. Biodiversitas 18: 1-9. Bacterial wilt on chili cause by Ralstonia solanacearum. This disease is important, causing plant death and significant yield losses. Biological control is desirable because control with other methods gives variable results. One of the important group of biological agent is the plant growth pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 16 publications
1
33
0
5
Order By: Relevance
“…One pure colony of indigenous endophyte bacteria (IEB) isolates was added to 25mL of Tryptic Soy Broth (TSB, HiMedia®) in culture bottle (50mL) and was incubated in rotary shaker for 24 hours. 1 mL preculture was transferred to 150 mL of sterile coconut water in Erlenmeyer flask for main culture and was incubated for 2x24 hours (Yanti et al 2017). Suspension of IEB isolates from main culture was diluted with comparison to McFarland scale 8 (Density estimated 10 8 CFU/mL).…”
Section: Multiplication Of Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…One pure colony of indigenous endophyte bacteria (IEB) isolates was added to 25mL of Tryptic Soy Broth (TSB, HiMedia®) in culture bottle (50mL) and was incubated in rotary shaker for 24 hours. 1 mL preculture was transferred to 150 mL of sterile coconut water in Erlenmeyer flask for main culture and was incubated for 2x24 hours (Yanti et al 2017). Suspension of IEB isolates from main culture was diluted with comparison to McFarland scale 8 (Density estimated 10 8 CFU/mL).…”
Section: Multiplication Of Isolatesmentioning
confidence: 99%
“…Our Previous study had screened 9 best endophyte bacteria isolates, which has potential to plant growth promotion (Yanti et al 2017). However, the ability of these strain to control pathogens is not identified, yet.…”
Section: Introductionmentioning
confidence: 99%
“…and their in vitro inhibition zones might be due to the activity of lytic enzymes like protease and the synthesis of antibiotics, which are the most common characteristics associated with PGPR (Mazurier et al 2009). Based on properties of strains, only little direct activities showed being related to biocontrol activity, whereas from previous research (Yanti et al 2017), all isolates showed the best biocontrol activity with no R. solanacearum symptoms appears. Based on these results, it could be concluded that most of all strains had ability in controlling R. solanacearum via indirectly mechanisms such as Induced Systemic Resistance (ISR).…”
Section: Discussionmentioning
confidence: 67%
“…The Hypersensitive reactions were done by infiltrating the Mirabilis jalapa leaves with 10 8 CFU/mL, which was acquired by comparing McFarland solutions in the scale of 8. The infiltrated leaves were then incubated for 48 hours (Yanti et al 2017). The occurrence of necrosis on the M. jalapa leaves indicated the positive HR reactions of Bacillus, which was suspected as pathogens so that it could not be used further.…”
Section: Hypersensitive (Hr) Reactionmentioning
confidence: 99%
See 1 more Smart Citation